Research Progress on the GIP/GLP-1 Receptor Coagonist Tirzepatide, a Rising Star in Type 2 Diabetes. (15th April 2023) - Ma, Zijun; Jin, Kaiqin; Yue, Mengmeng; Chen, Xin; Chen, Jun
Abstract : Type 2 diabetes mellitus (T2DM) is a chronic progressive metabolic disease that has become a growing health problem worldwide, and the dangers of hyperglycemia and its chronic complications have long been considered a goal of diabetes treatment. In recent years, tirzepatide has become the first dual GIP/GLP-1R agonist approved for the treatment of diabetes mellitus in the United States as a new hypoglycemic medicine. Its hypoglycaemic and weight loss effects have been demonstrated in several large clinical trials, and there is also evidence that it has great potential for cardiovascular protection. In addition, the very concept of synthetic peptides opens up many unknown possibilities for tirzepatide. Ongoing trials (NCT04166773 ) and evidence suggest that it appears to be a promising drug in the areas of NAFLD, renal, and neuroprotection. Based on preclinical studies and clinical trials, the aim of this article is to discuss the latest clinical developments in tirzepatide, to focus on its differences with other incretin therapies, and to suggest future possibilities and mechanisms of tirzepatide therapy.